Self-organization and nonlocal nature of geophysical turbulence and planetary boundary layers - S. S. Zilitinkevich (Геофизический журнал, 2010)
The classical paradigm of the theory of turbulence states that any turbulent flow can be considered as a superposition of the fully organized mean motion and the fully chaotic turbulence is characterized by the direct energy cascade (from larger to smaller eddies). Accordingly, the key tools for modeling geophysical flows are the concepts of the down-gradient turbulent transport (analogous to the molecular transport); the Kolmogorov theory of the inertial interval in the turbulence spectra; and, in atmospheric boundary-layer modeling, the Monin-Obukhov similarity theory. These tools have made a good showing as applied to a wide range of neutrally or weakly stratified geophysical and engineering flows. However, in strongly stable and especially in unstable stratification they face insurmountable difficulties. The point is that the very-high-Reynolds-number geophysical flows almost always include a type of chaotic motions, “strange turbulence”, missed in the classical theory and are characterized by the inverse energy cascade: from smaller to larger eddies, which leads to the self-organization in the form of long-lived, large-scale motions coexisting with the usual mean flow. The proposed new paradigm accounts for the strange turbulence and organized structures as additional inherent features of turbulent flows.